The Effect of Circulation of 3% HCL Solution On the Corrosion Rate of Aluminum - Ismet Eka Putra; Teguh Burhanuddin (Jurnal Teknik Mesin, 2020)
Corrosion is usually called rusting. Corrosion to aluminum is carried out by circulating and non-circulating methods. The specimens were placed in 3% HCl solution, each with 3 specimens in one vessel. There are 9 specimens in 3 vessels. In this study, aluminum was immersed with a circulation of 385 L/hour and 432 L/hour and also without circulation with immersion time for 4 days. The highest corrosion rate was obtained in aluminum soaked in 3% HCl for 4 days with a circulation of 432 L / hour, 0.5215 Mpy. The lowest corrosion rate was obtained for aluminum immersed in 3% HCl for 4 days without circulation, 0.1830 Mpy.